Krein's method in inverse scattering - Ramm, Alexander G. (American Mathematical Society, 2000)
A detailed discussion of the Krein’s results (applicable for solving the inverse scattering problem) is given with complete proofs. It is shown that the S-function S(k) used in Krein’s work is the S-matrix used in physics. The basic new results of the paper include the detailed description and analysis of an inversion algorithm based on Krein’s results and a proof of its consistency, that is the proof that the reconstructed potential generates the same scattering data from which it was reconstructed. Numerical advantages of using Krein’s method are discussed.
Keywords: Krein's method; Inverse scattering; Inversion algorithm